Upaya Meningkatkan Hasil Belajar Ekonomi Siswa Materi Pendapatan Nasional Melalui Model Pembelajaran Problem Based Learning di Kelas Ekonomi Lintas Minat XI IPA1 SMA Negeri 1 Candung - May Afdaryanti (Departement of Mathematics Education, 2022)
This study aims to obtain information and discuss the Efforts to Improve Student Economics Learning Outcomes on National Income Materials through the Problem Based Learning Model in Cross-Interest Economics Class XI IPA1 SMA Negeri 1 Cdungung. This type of research is classroom action research (CAR). The research location was at CMAN 1 SMAN 1, Agam Regency. The subjects in this study were 23 students in cross-interest economics class XI IPA1. The research was carried out in the odd semester of the 2021/2022 school year which began in July 2021. Data collection techniques in this study were carried out using observation, field notes, student worksheets, and documentation. Data analysis techniques use percentage formulas and data reduction. The results showed that the Problem Based Learning learning model had a positive impact on improving student learning outcomes in cross-interest economic class XI IPA1. This can be seen from the students' understanding and mastery of the material that has been conveyed by the teacher so far (learning completeness increased from the pre-cycle, cycle I and cycle II, namely 29%, 64% and 86% respectively by giving gifts